Scientific Artical of the Lecturers from the Faculty for Sport and Physical Education in Niksic Published in the Journal Sport Mont between 2016 and 2018: A Content Analysis - Boris Banjevic (Journal of Anthropology of Sport and Physical Education, 2019)
Sport Mont is a scientific journal which has been existing since 2003 and it has published a great number of works of renowned scientists in the field of sport sciences and medicine. The journal has been indexed in more international database, it is released three times a year, and the published works are mostly presented on the scientific conference of the Montenegrin Sport Academy. Sport Mont, in addition to the original scientific works, publishes reviews, editorials, short reports, as well as the calls and awards for works in the field of sport sciences and medicine. This essay deals with the contents analysis of the scientific research works where the authors and co-authors are the lecturers of the Faculty for Sport and Physical Education in Nikšić, published in the journal Sport Mont between 2016 and 2018. They have been sorted according to the scientific fields they belong to, and through discussion, a short overview of the obtained results has been given. This way makes possible an easier search of the mentioned articles for the authors who express their interest for them.